The effects of income fluctuations on rural health and nutrition - Kosec, Katrina; Song, Jie (International Food Policy Research Institute, 2019)
This study explores the effects of fluctuations in household income on health and nutrition outcomes from birth to adulthood. We analyze data from a nationally representative, 13 year rolling panel dataset from Kyrgyzstan spanning 2004–2016. We address the endogeneity of income by instrumenting for income with predicted income, obtained using the household’s initial period share of income from different sources and aggregate growth rates over time in each source. Young children (age 0-5) exposed to reductions in income experienced reductions in height that were largest for girls and those under age two—groups that additionally experienced increases in stunting. Reduced consumption of healthy foods, reduced dietary diversity, and less expenditure on health may help explain the results. A channel possibly offsetting negative impacts is a decrease in fertility. At the same time, older children and adults saw decreases in BMI and—for adults—decreases in the incidence of overweight.